FAVQULODDA VAZIYATLARDA KONSTRUKSIYA STERJENLARIDAGI MUSTAHKAMLIK SHARTLARI - E.Vassiyev (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article shows different resistance to stretching or compression of  structural  elements  and  struts  during  emergency  situations.  Normal  stress, allowable stresses are given. In emergency situations, the stability of the system of jibs connected by means of hinges was checked and calculated. The thickness of the wall of the structure is determined, and the permissible stress for compression of cast iron is given.